Role of DTL in Hepatocellular Carcinoma and Its Impact on the Tumor Microenvironment - Li, Zuyin; Wang, Rangrang; Qiu, Chen; Cao, Can; Zhang, Jianming; Ge, Jun; Shi, Yuanping (Frontiers in Immunology, 2022)
Background: The crucial role of DTL has been previously implicated in genomic stability, however, its prognostic value and its relation with tumor immunity in hepatocellular carcinoma (HCC) remain to be further explored. Methods: Transcriptional and mutational datasets as well as clinical information were retrieved from the GEO, ICGC and TCGA databases. Differentially expressed genes (DEGs) were obtained from the comparasion DTLhigh and DTLlow expression groups of TCGA-HCC cohort. Those genes were under KEGG and gene ontology (GO) analysis to decipher the influence of DTL gene on the biological behavior of HCC tumor cells. Survival status and mutational characteristics of patients according to DTL levels were depicted and analyzed. The DTL overexpression in HCC and its impact on prognosis were further confirmed by a cohort of 114 HCC patients (Validation cohort). TIMER, GEPIA and TISIDB databases were adopted to investigate the potential relations between DTL levels and the status of immune cells, as well as immune cell infiltrations. Results: DTL gene is overexpressed in tumor tissues compared with distant non-malignant liver tissues, and DTL overexpression in HCC would enhance the HCC cells in the activities of cell cycle and division. HCC patients with high DTL expression have unfavorable clinical outcomes and harbor more somatic mutations than those with low DTL expression, and multivariate analysis also revealed that DTL overexpression could act as an independent biomarker for prognosis. Moreover, DTL gene was positively linked to marker sets of infiltrating activated CD8+ and CD4+ T cells, however, these cells demonstrated functionally exhausted. Conclusions: Patients with DTL overexpression phenotype in HCC have poorer prognosis than those in DTLlow group due to the role of DTL gene in the process of pro-cell proliferation, accompanying with the immunosuppressive microenvironment and T cell exhaustion.